Subnational trade flows and state-level energy intensity: an empirical analysis - P. Chintrakarn (2018)
In one strand of research, analysts examine the trends and determinants of energy usage and intensity. In the second strand, researchers analyse the impact of trade flows on environmental outcomes. Recently, Cole (2006) bridges this gap, analysing the impact of trade intensity on energy usage utilizing panel data at the country level. In line with Cole (2006), we analyse the impact of subnational trade flows across US states on state-level energy usage and intensity, controlling for the endogeneity of trade flows. The model treating trade as endogenous confirms the cross-country result in Cole (2006); trade causes energy intensity to rise on average. However, the impact is not homogeneous across sectors as the increase in intensity is concentrated in the industrial and transportation sectors. © 2013 Copyright Taylor and Francis Group, LLC.